High-frequency supercapacitors based on doped carbon nanostructures - Han, Z; Huang, C; Meysami, S; Piche, D; Seo, D; Pineda, S; Murdock, A; Bruce, P; Grant, P; Grobert, N (Elsevier, 2017)
Carbon nanostructures are promising materials for electrochemical energy storage but their frequency response is usually poor, limiting their utilization in high-frequency applications. Here we demonstrate the growth of carbon nanostructures with different dopants of N, B, P/N, B/N, and Si, based on a scalable aerosol-assisted chemical vapor deposition process. The doped carbon nanostructures were directly grown on the conductive Ni substrates and exhibit an open and porous structure which is beneficial for fast ion transport and ion kinetics. Coin cells made of the doped carbon nanostructures demonstrate a frequency response as fast as 13,200 Hz at a phase angle of −45° and the smallest relaxation time constant of ∼77 μs. Together with a low equivalent series resistance and a large areal capacitance, the high-frequency supercapacitors based on doped carbon nanostructures could be promising in replacing traditional aluminium electrolytic capacitors for many high-frequency electronic devices.